If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -5 = 2x + -5 Reorder the terms: -5 + 8x = 2x + -5 Reorder the terms: -5 + 8x = -5 + 2x Add '5' to each side of the equation. -5 + 5 + 8x = -5 + 5 + 2x Combine like terms: -5 + 5 = 0 0 + 8x = -5 + 5 + 2x 8x = -5 + 5 + 2x Combine like terms: -5 + 5 = 0 8x = 0 + 2x 8x = 2x Solving 8x = 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 8x + -2x = 2x + -2x Combine like terms: 8x + -2x = 6x 6x = 2x + -2x Combine like terms: 2x + -2x = 0 6x = 0 Divide each side by '6'. x = 0 Simplifying x = 0
| 3-386+2= | | 4y+1y=13 | | x+1x+9=23 | | .38=2b+25*(-7) | | 17x^17=0 | | (Y-3)(Y^2+BY+C)=Y^3-27 | | 19(3-v)+10v=-15 | | -4(6x-7)-3(4+2x)= | | 3x+45=3(x-3) | | 6X(2x-1)= | | 3(2x-y)+6y= | | 0.3(y+4)=0.4(y-2) | | 19=35+9x | | 2(-1)-4-y=12 | | 3y-(y+2x)+x= | | 6y-9-3y+8=0 | | 2(0)-4-y=12 | | 4y-5x=4 | | 2(1)-4-y=12 | | 2z-18-4z=-9 | | -7+u=3 | | y-53=294 | | X^2+6x+6.75=0 | | 4x+7x-3=0 | | -101=w+5.3 | | -0.8k-3.1=.5 | | 4(2x-1)-(3-1)=3 | | 9x^2+18x=22 | | 4(2x-1)-(3x-1)=3 | | x+2/4=27/12 | | F(x)=x*2-6x-15 | | 31=7c+-74 |